"An ocean of knowledge:" Vai's transnational feminist alliances. Issue 4 (19th May 2021) - Gauthier, Jennifer L.
ABSTRACT: Using transnational feminist media theories, theories of Fourth Cinema, and Pacific Islander epistemology, this paper argues that the film Vai (2019) builds transnational feminist alliances among the peoples of the Pacific Islands. Made by a collective of nine women from across the Pacific, the film follows the life of Vai, a Pasifika woman who struggles to maintain connections to her family, culture and land. I argue that Indigenous media, particularly media made by Indigenous women, plays a powerful role in battles for Indigenous sovereignty and self-determination.